Influence of TYK2 in systemic sclerosis susceptibility: a new locus in the IL-12 pathway - Lopez-Isac, Elena; Campillo-Davo, Diana; Bossini-Castillo, Lara; Guerra, Sandra G.; Assassi, Shervin; Pilar Simeon, Carmen; Carreira, Patricia; Ortego-Centeno, Norberto; Garcia De La Pena, Paloma; Beretta, Lorenzo; Santaniello, Alessandro; Bellocchi, Chiara; et al. (Annals of the Rheumatic Diseases, 2016)
TYK2 is a common genetic risk factor for several autoimmune diseases. This gene encodes a protein kinase involved in interleukin 12 (IL-12) pathway, which is a well-known player in the pathogenesis of systemic sclerosis (SSc). Therefore, we aimed to assess the possible role of this locus in SSc.This study comprised a total of 7103 patients with SSc and 12 220 healthy controls of European ancestry from Spain, USA, Germany, the Netherlands, Italy and the UK. Four TYK2 single-nucleotide polymorphisms (V362F (rs2304256), P1104A (rs34536443), I684S (rs12720356) and A928V (rs35018800)) were selected for follow-up based on the results of an Immunochip screening phase of the locus. Association and dependence analyses were performed by the means of logistic regression and conditional logistic regression. Meta-analyses were performed using the inverse variance method.Genome-wide significance level was reached for TYK2 V362F common variant in our pooled analysis (p=3.08×10(-13), OR=0.83), while the association of P1104A, A928V and I684S rare and low-frequency missense variants remained significant with nominal signals (p=2.28×10(-3), OR=0.80; p=1.27×10(-3), OR=0.59; p=2.63×10(-5), OR=0.83, respectively). Interestingly, dependence and allelic combination analyses showed that the strong association observed for V362F with SSc, corresponded to a synthetic association dependent on the effect of the three previously mentioned TYK2 missense variants.We report for the first time the association of TYK2 with SSc and reinforce the relevance of the IL-12 pathway in SSc pathophysiology.
EVALuna2:13153